ANALISIS PERBANDIGAN KINERJA KEUANGAN ANTARA BANK BRI, BNI, BTN DAN MANDIRI PADA TAHUN 2012-2020 - Erytria Meylina; Banu Witono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this paper is to find out whether there is a comparison of financial performance seen from the ratio of Net Profit Margin(NPM), Return Of Assets(ROA), Return Of Equity(ROE) and Non Performing Loan(NPL) at state-owned banks(BUMN) in Indonesia for the period 2012-2020. This type of research is quantitative. Research thet uses secondary data in the form of annual financial reports. This study uses a saturated sample of 4 state-owned banks in Indonesia for the period 2012-2020 with the determination of the sample using the documentation method and testing is carried out with a significant value of 5%. The data analysis technique in this study used data normality testing, hypothesis testing and hypothesis testing with data processing using the Statistical Package for Social Science(SPSS) version 21 application. Based on the results of data analysis, the ratio of Net Profit Margin, Return Of Assets, Return Of Equity, Non Performing Loans there are significant differences between the four state-owned banks.